Foamable urethane resin composition and polyurethane foamed article
The foamable urethane resin composition with red phosphorus and other flame retardants addresses the issues of flame spread and handling in polyurethane foams, providing effective fire resistance and improved manageability.
Patent Information
- Application Number
- JP2024196003
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-24
AI Technical Summary
Existing polyurethane foams used as insulation materials in buildings face issues with flame spread and handling properties, becoming brittle and difficult to manage when excessive flame retardants are added to enhance fire resistance.
A foamable urethane resin composition containing specific amounts of red phosphorus and other flame retardants, along with a polyol compound, polyisocyanate compound, foam stabilizer, and blowing agent, is formulated to achieve a steel ball sinking distance of 20 mm or less, ensuring effective flame retardancy and improved handling.
The composition produces polyurethane foam that prevents flame spread and maintains structural integrity during fires, with enhanced handling properties and reduced brittleness.
Smart Images

Figure 2025013625000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a foamable urethane resin composition and a polyurethane foam made from the same. [Background technology]
[0002] Polyurethane foams are used to insulate and prevent condensation on ceilings, roofs, and walls of buildings such as apartment complexes, detached houses, and commercial buildings, taking advantage of their excellent heat insulating properties. Although polyurethane foams are lightweight, they are organic and therefore flammable. To improve this, polyurethane foams containing flame retardants and the like to enhance their flame retardancy are used. For example, Patent Document 1 describes a flame-retardant polyurethane foam obtained by using ammonium polyphosphate, a urea derivative, a polyol, and an isocyanate. The flame-retardant polyurethane foam is characterized by using ammonium polyphosphate in the range of 5 to 150 parts by weight and a urea derivative in the range of 0.001 to 15 parts by weight per 100 parts by weight of polyol. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-151524 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there have been a relatively large number of reports of fires caused by polyurethane foams used as thermal insulation materials in buildings. In order to alleviate such problems, it is hoped that polyurethane foams that not only have excellent flame retardancy but also have the property of being less susceptible to the spread of fire when a fire breaks out will be developed. In addition, although using a large amount of flame retardant makes it easier to obtain a polyurethane foam that is resistant to the spread of fire, the foam becomes brittle and its surface easily cracks, making it prone to buckling and difficult to handle. Accordingly, an object of the present invention is to provide a foamable urethane resin composition for producing a polyurethane foam that has flame-spread resistance and excellent handleability, and a polyurethane foam made from the same. [Means for solving the problem]
[0005] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a foamable urethane resin composition containing a polyol compound, a polyisocyanate compound, a foam stabilizer, a blowing agent, a catalyst, and an additive, the additive containing a specific amount of red phosphorus, and the composition having a sinking distance of a steel ball equal to or less than a certain value, and have completed the present invention. That is, the present invention provides the following [1] to [8]. [1] A foamable urethane resin composition comprising a polyol compound, a polyisocyanate compound, a foam stabilizer, a blowing agent, a catalyst, and an additive, wherein the additive comprises red phosphorus, the content of the red phosphorus being more than 0 part by mass and less than 5 parts by mass per 100 parts by mass of a urethane resin composed of the polyol compound and the polyisocyanate compound, and a polyurethane foam composed of the foamable urethane resin composition exhibits a sinking distance of a steel ball of 20 mm or less in a steel ball sinking test described below. (Steel ball sinking evaluation) (1) Cut the polyurethane foam into a cube with sides of 50 mm to use as a test specimen. (2) Place a wire mesh 30 mm from the burner port of a Bunsen burner (outer flame length 70 mm). Place a steel ball with a diameter of 4.7 mm and a weight of 0.44 g on the wire mesh and heat it for at least 5 minutes until the entire steel ball turns red, raising the temperature of the steel ball to 750°C or higher. (3) In an atmosphere of 23°C, the steel ball heated in (2) above is immediately placed on the center of the upper part of the test piece in (1) above and left there until the steel ball has completely sunk in. Next, the cross section of the test piece that has been sufficiently cooled is cut and the sinking distance of the steel ball is measured. [2] The polyurethane foam made of the foamable urethane resin composition described in [1] above is subjected to a test for a radiant heat intensity of 50 kW / m2 in accordance with the test method of ISO-5660. 2 When heated at 40°C, the total heat generated after 5 minutes is 8MJ / m 2 The foamable urethane resin composition according to the above [1], [3] The foamable urethane resin composition according to the above [1] or [2], wherein the catalyst comprises a trimerization catalyst. [4] The foamable urethane resin composition according to any one of the above [1] to [3], having an isocyanate index of 200 to 700. [5] The foamable urethane resin composition according to any one of the above [1] to [4], wherein the additive contains a solid flame retardant other than red phosphorus, and the total content of the red phosphorus and the solid flame retardant other than red phosphorus is 0.5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the urethane resin composed of the polyol compound and the polyisocyanate compound. [6] The foamable urethane resin composition according to any one of the above [1] to [5], wherein the polyol compound is an aromatic polyol compound. [7] The foamable urethane resin composition according to the above [6], wherein the aromatic polyol compound contains at least one of a phthalic acid-based polyester polyol and an amine-based polyether polyol. [8] A polyurethane foam formed from the foamable urethane resin composition according to any one of [1] to [7] above, wherein the steel ball has a sinking distance of 20 mm or less in the steel ball sinking evaluation. Effect of the Invention
[0006] According to the present invention, it is possible to provide a foamable urethane resin composition capable of producing a polyurethane foam that has the property of being resistant to the spread of fire in the event of a fire and has good handleability, and a polyurethane foam made from the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] [Foamable urethane resin composition] The foamable urethane resin composition of the present invention is a composition containing a polyol compound, a polyisocyanate compound, a foam stabilizer, a blowing agent, a catalyst, and an additive, the additive containing red phosphorus, the content of red phosphorus being more than 0 and less than 5 parts by mass per 100 parts by mass of a urethane resin composed of the polyol compound and the polyisocyanate compound (hereinafter simply referred to as 100 parts by mass of the urethane resin). Furthermore, the sinking distance of a steel ball in the steel ball sinking test described below for a polyurethane foam composed of the foamable urethane resin composition is 20 mm or less. (Steel ball sinking evaluation) (1) Cut the polyurethane foam into a cube with sides of 50 mm to use as a test specimen. (2) A wire mesh is placed 30 mm from the burner port of a Bunsen burner (outer flame length 70 mm), and a steel ball with a diameter of 4.7 mm and a weight of 0.44 g is placed on the wire mesh and heated for at least 5 minutes until the entire steel ball turns red, and the temperature of the steel ball is 750°C or higher. The Bunsen burner uses LPG combustion gas. (3) In an atmosphere of 23°C, the steel ball heated in (2) above is immediately placed on the center of the upper part of the test piece in (1) above and left there until the steel ball has completely sunk in. Next, the cross section of the test piece that has been sufficiently cooled is cut and the sinking distance of the steel ball is measured.
[0008] In the above steel ball sinking evaluation, as long as the diameter and weight of the steel ball are within the ranges of 4.7±0.5 mm and 0.44±0.5 g, and the other conditions are as described above, an equivalent steel ball sinking evaluation will be obtained, so the evaluation may be performed within these diameter and weight ranges. The outer flame length means the length of the flame directly above the center of the burner port.
[0009] In the polyurethane foam made of the foamable urethane resin composition of the present invention, the sinking distance of the steel ball in the steel ball sinking evaluation is 20 mm or less. If the sinking distance of the steel ball exceeds 20 mm, the polyurethane foam is likely to spread fire when exposed to fire, etc., and it becomes difficult to effectively prevent the fire from spreading. From the viewpoint of effectively preventing the fire from spreading, the sinking distance of the steel ball is preferably 15 mm or less, more preferably 10 mm or less, and even more preferably 5 mm or less. The sinking distance of the steel ball is 0 mm or more. The steel ball sinking distance can be adjusted to a desired value by adjusting the type of polyol compound contained in the foamable urethane resin composition, the content of red phosphorus, the content of flame retardants other than red phosphorus, and the like.
[0010] The polyurethane foam used in the steel ball sinking evaluation is prepared under the conditions described in the Examples.
[0011] (Total heat generation) The polyurethane foam made of the foamable urethane resin composition of the present invention was subjected to a test for a radiation heat intensity of 50 kW / m according to the test method of ISO-5660. 2 When heated at 40°C, the total heat generated after 5 minutes is 8MJ / m 2 The total calorific value is preferably 8MJ / m or less. 2 The polyurethane foam made of the foamable urethane resin composition of the present invention has a predetermined flame retardancy because the polyurethane foam has a predetermined flame retardancy and the steel ball sinking distance is equal to or less than a certain value as described above, so that the polyurethane foam has both flame retardancy and the property of not spreading fire, and can more effectively prevent the spread of fire in the event of a fire. From the viewpoint of further improving the flame retardancy of the polyurethane foam, the total calorific value is set to 7 MJ / m 2 It is preferable that the concentration is less than 5MJ / m 2 It is more preferable that: The gross calorific value is obtained by a cone calorimeter test, and specifically, can be measured by the method described in the Examples. In the above-mentioned cone calorimeter test, it is preferable that the polyurethane foam used in the test has a shape stability to such an extent that it does not come into contact with the spark igniter of the cone calorimeter.
[0012] (red phosphorus) The additive contained in the foamable urethane resin composition of the present invention contains red phosphorus. Red phosphorus functions as a solid flame retardant, and there is no limitation on the type thereof, and a commercially available product can be appropriately selected and used. The red phosphorus may be a simple substance, but it is not necessary to be a simple substance, and it may be appropriately surface-treated. The content of the red phosphorus is more than 0 parts by mass and less than 5 parts by mass with respect to 100 parts by mass of the urethane resin. By containing a certain amount or more of red phosphorus, the flame retardancy of the polyurethane foam is enhanced. In addition, by making the content of red phosphorus less than 5 parts by mass, the foamability is improved, and the polyurethane foam formed is less likely to buckle, and has excellent handleability. From this viewpoint, the content of red phosphorus is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and preferably 4.5 parts by mass or less with respect to 100 parts by mass of the urethane resin.
[0013] In addition, when the foamable urethane resin composition contains a solid flame retardant other than red phosphorus, which will be described later, the total content of red phosphorus and the solid flame retardant other than red phosphorus is preferably 0.5 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the urethane resin. By making the total amount of red phosphorus and the solid flame retardant other than red phosphorus 0.5 parts by mass or more, even if the polyurethane foam is exposed to high temperatures, the shape change is suppressed, and the generation of combustion gas from the polyurethane foam is suppressed, thereby enhancing the flame retardancy of the polyurethane foam. In addition, by making the total amount of red phosphorus and the solid flame retardant other than red phosphorus 10 parts by mass or less, the load on the foaming machine, such as wear caused by the solid flame retardant, is reduced, and the foaming property is improved, and the polyurethane foam formed is less likely to buckle, resulting in excellent handleability. From this viewpoint, the total content of red phosphorus and the solid flame retardant other than red phosphorus is preferably 1 part by mass or more, more preferably 2 parts by mass or more, even more preferably 3 parts by mass or more, and preferably 9 parts by mass or less, more preferably 8 parts by mass or less with respect to 100 parts by mass of the urethane resin.
[0014] (Polyol Compound) The polyol compound contained in the foamable urethane resin composition of the present invention is not particularly limited, but polyether polyols and polyester polyols are preferred. Among them, aromatic polyol compounds such as aromatic polyether polyols and aromatic polyester polyols are preferred from the viewpoint of improving the flame retardancy of the resulting polyurethane foam, as described below.
[0015] <Polyether polyol> Polyether polyol is a polyoxyalkylene polyol obtained by ring-opening addition polymerization of an alkylene oxide to an initiator having two or more active hydrogen atoms. Specific examples of the initiator include aliphatic polyhydric alcohols (e.g., glycols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexylene glycol, and cyclohexanedimethanol, triols such as trimethylolpropane and glycerin, and tetrafunctional alcohols such as pentaerythritol), aliphatic amines (e.g., alkylenediamines such as ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, and neopentyldiamine, and alkanolamines such as monoethanolamine and diethanolamine), and aromatic amines (e.g., aniline, tolylenediamine, xylylenediamine, diphenylmethanediamine, and Mannich condensation products), and the like. These may be used alone or in combination of two or more. As the polyether polyol, from the viewpoint of enhancing the flame retardancy of the polyurethane foam, an aromatic polyether polyol having an aromatic ring in the molecule is preferred, and among them, an amine-based polyether polyol such as a tolylenediamine-based polyether polyol or a Mannich-based polyether polyol is preferred, with the Mannich-based polyether polyol being more preferred. The tolylenediamine-based polyether polyol is a polyether polyol obtained by using tolylenediamine as an initiator. The Mannich-based polyether polyol is a polyether polyol produced by utilizing the Mannich reaction of phenols, primary or secondary amines, and aldehydes, such as a polyether polyol obtained by using a Mannich condensate as an initiator.
[0016] The hydroxyl value of the polyether polyol is preferably from 200 to 1000 mgKOH / g, and more preferably from 300 to 600 mgKOH / g. The hydroxyl value is a value measured in accordance with JIS K1557-1:2007.
[0017] <Polyester polyol> Examples of polyester polyols include aromatic polyester polyols and aliphatic polyester polyols, but when considering the flame retardancy of the resulting polyurethane foam, it is preferable to use aromatic polyester polyols. The aromatic polyester polyol is preferably a condensate of an aromatic dicarboxylic acid such as o-phthalic acid (phthalic acid), m-phthalic acid (isophthalic acid), p-phthalic acid (terephthalic acid), or naphthalenedicarboxylic acid with a glycol. Among them, from the viewpoint of increasing the flame retardancy of the polyurethane foam, decreasing the value of the steel ball sinking distance described above and improving the flame-spreading performance, and from the viewpoint of suppressing buckling and improving handleability, a phthalic acid-based polyester polyol that is a condensate of at least one of o-phthalic acid, m-phthalic acid, and p-phthalic acid with a glycol is preferred, and a p-phthalic acid-based polyester polyol that is a condensate of p-phthalic acid and a glycol is more preferred. The glycol is not particularly limited, but it is preferable to use low molecular weight aliphatic glycols known as components of polyester polyols, such as ethylene glycol, propylene glycol, and diethylene glycol.
[0018] Among the above-mentioned polyol compounds, from the viewpoint of increasing the flame retardancy of the polyurethane foam and decreasing the above-mentioned steel ball sinking distance and increasing the flame-spreading resistance, aromatic polyol compounds are preferred, and it is more preferred that the aromatic polyol compound contains at least one of a phthalic acid-based polyester polyol and an amine-based polyether polyol. The aromatic polyol compound is preferably a phthalic acid-based polyester polyol, and more preferably a p-phthalic acid-based polyester polyol.
[0019] The hydroxyl value of the polyester polyol is preferably from 100 to 400 mgKOH / g, and more preferably from 150 to 350 mgKOH / g.
[0020] The polyol compound preferably contains an aromatic polyol compound in an amount of 50% by mass or more, more preferably 80% by mass or more, and even more preferably 100% by mass. The aromatic polyol compound preferably contains 50% by mass or more, more preferably 80% by mass or more, and even more preferably 100% by mass of at least one of a phthalic acid-based polyester polyol and an amine-based polyether polyol.
[0021] (Polyisocyanate compounds) As the polyisocyanate compound contained in the foamable urethane resin composition, various polyisocyanate compounds having two or more isocyanate groups, such as aromatic, alicyclic, and aliphatic polyisocyanate compounds, can be used. It is preferable to use liquid diphenylmethane diisocyanate (MDI) because of ease of handling, rapid reaction, excellent physical properties of the resulting polyurethane foam, and low cost. Examples of liquid MDI include crude MDI (also called polymeric MDI). Specific examples of commercially available liquid MDI include "44V-10" and "44V-20" (manufactured by Sumika Covestro Urethane Co., Ltd.), and "Millionate MR-200" (Nippon Polyurethane Industry Co., Ltd.). In addition, uretonimine-containing MDI (for example, a commercially available product "Millionate MTL": manufactured by Nippon Polyurethane Industry Co., Ltd.) may also be used. In addition to liquid MDI, other polyisocyanate compounds may be used in combination, and as the polyisocyanate compounds to be used in combination, any polyisocyanate compound known in the technical field of polyurethanes can be used without any limitations.
[0022] The isocyanate index (NCO INDEX) in the foamable urethane resin composition is not particularly limited, but is preferably from 200 to 700, more preferably from 250 to 500, and even more preferably from 250 to 400, from the viewpoint of improving flame retardancy. Here, the isocyanate index means the equivalent ratio of the isocyanate groups of the polyisocyanate compound to all active hydrogen groups contained in the foamable urethane resin composition (water as a foaming agent is calculated as a bifunctional active hydrogen compound) expressed as a percentage (the equivalent ratio of isocyanate groups to 100 equivalents of active hydrogen groups).
[0023] (Additives) The foamable urethane resin composition of the present invention contains an additive, and the additive contains red phosphorus as described above. The additive preferably contains a flame retardant other than red phosphorus. The flame retardant other than red phosphorus is not particularly limited, but is preferably at least one selected from a phosphate-based flame retardant, a boron-containing flame retardant, a bromine-containing flame retardant, a phosphate-containing flame retardant, an antimony-containing flame retardant, a phosphinic acid-based flame retardant, and a metal hydroxide-based flame retardant. As the flame retardant other than red phosphorus, it is preferable to use at least one of a solid flame retardant and a liquid flame retardant, and it is preferable to use both, and it is particularly preferable to use a boric acid-containing flame retardant as the solid flame retardant and a phosphate ester-based flame retardant as the liquid flame retardant, which will be described later, in combination. Here, the solid flame retardant refers to a flame retardant that is solid at 23° C., and the liquid flame retardant refers to a flame retardant that is liquid at 23° C.
[0024] Examples of the solid flame retardant include a boron-containing flame retardant, a bromine-containing flame retardant, a phosphate-containing flame retardant, an antimony-containing flame retardant, a phosphinic acid-based flame retardant, a metal hydroxide-based flame retardant, etc. Among them, a boron-containing flame retardant and a bromine-containing flame retardant are preferred, and a boron-containing flame retardant is more preferred. By using a solid flame retardant, it is possible to suppress deformation of the polyurethane foam when it is exposed to heat.
[0025] <Boron-containing flame retardants> Specific examples of the boron-containing flame retardant include alkali metal borate such as lithium borate, sodium borate, potassium borate, and cesium borate, alkaline earth metal borate such as magnesium borate, calcium borate, and barium borate, zirconium borate, zinc borate, aluminum borate, and ammonium borate, etc. Among these, zinc borate is preferred.
[0026] <Brominated flame retardants> The brominated flame retardant is not particularly limited as long as it is a compound containing bromine in its molecular structure, and examples thereof include aromatic brominated compounds. Specific examples of the aromatic brominated compound include monomeric organic bromine compounds such as hexabromobenzene, pentabromotoluene, hexabromobiphenyl, decabromobiphenyl, hexabromocyclodecane, decabromodiphenyl ether, octabromodiphenyl ether, hexabromodiphenyl ether, bis(pentabromophenoxy)ethane, ethylene bis(pentabromophenyl), ethylene bis(tetrabromophthalimide), and tetrabromobisphenol A; polycarbonate oligomers produced using brominated bisphenol A as a raw material; and mixtures of the polycarbonate oligomers and bisphenols. Examples of the brominated epoxy compounds include brominated polycarbonates such as copolymers with brominated bisphenol A, diepoxy compounds produced by the reaction of brominated bisphenol A with epichlorohydrin, and monoepoxy compounds obtained by the reaction of brominated phenols with epichlorohydrin, and halogenated bromine compound polymers such as poly(brominated benzyl acrylate), brominated polyphenylene ether, brominated bisphenol A, condensates of cyanuric chloride and brominated phenol, brominated (polystyrene), poly(brominated styrene), brominated polystyrenes such as crosslinked brominated polystyrene, and crosslinked or non-crosslinked brominated poly(α-methylstyrene). Among these, ethylene bis(pentabromophenyl), ethylene bis(tetrabromophthalimide), hexabromobenzene, and the like are preferable.
[0027] <Phosphate-containing flame retardants> Examples of the phosphate-containing flame retardant include phosphates consisting of a salt of phosphoric acid and at least one metal or compound selected from metals of Groups IA to IVB of the periodic table, ammonia, aliphatic amines, and aromatic amines. The phosphoric acid is not particularly limited, and examples thereof include various phosphoric acids such as monophosphoric acid, pyrophosphoric acid, and polyphosphoric acid. Examples of the metals in Groups IA to IVB of the periodic table include lithium, sodium, calcium, barium, iron (II), iron (III), aluminum, etc. Examples of the aliphatic amines include methylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, piperazine, etc. Examples of the aromatic amines include pyridine, triazine, melamine, etc. The above-mentioned phosphate-containing flame retardants may be subjected to a known water resistance improving treatment, such as treatment with a silane coupling agent or coating with a melamine resin.
[0028] Specific examples of phosphate-containing flame retardants include monophosphates, pyrophosphates, polyphosphates, and the like. The monophosphate salt is not particularly limited, and examples thereof include ammonium salts such as ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; sodium salts such as monosodium phosphate, disodium phosphate, trisodium phosphate, monosodium phosphite, disodium phosphite, and sodium hypophosphite; potassium salts such as monopotassium phosphate, dipotassium phosphate, tripotassium phosphate, monopotassium phosphite, dipotassium phosphite, and potassium hypophosphite; lithium salts such as monolithium phosphate, dilithium phosphate, trilithium phosphate, monolithium phosphite, dilithium phosphite, and lithium hypophosphite; barium salts such as barium dihydrogen phosphate, barium hydrogen phosphate, tribarium phosphate, and barium hypophosphite; magnesium salts such as monohydrogen magnesium phosphate, magnesium hydrogen phosphate, trimagnesium phosphate, and magnesium hypophosphite; calcium salts such as calcium dihydrogen phosphate, calcium hydrogen phosphate, tricalcium phosphate, and calcium hypophosphite; and zinc salts such as zinc phosphate, zinc phosphite, and zinc hypophosphite.
[0029] The polyphosphate is not particularly limited, but examples thereof include ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium amide polyphosphate, and aluminum polyphosphate. Among these, it is preferable to use monophosphates, and it is more preferable to use ammonium dihydrogen phosphate, since this improves the self-extinguishing property of the phosphate-containing flame retardant. The phosphate-containing flame retardants may be used alone or in combination of two or more.
[0030] <Antimony-containing flame retardants> Examples of the antimony-containing flame retardant used in the present invention include antimony oxide, antimonates, and pyroantimonates. Examples of antimony oxides include antimony trioxide and antimony pentoxide. Examples of antimonate salts include sodium antimonate and potassium antimonate. Examples of pyroantimonate salts include sodium pyroantimonate and potassium pyroantimonate. Preferably, the antimony-containing flame retardant is antimony oxide. The antimony-containing flame retardants may be used alone or in combination of two or more.
[0031] <Phosphinic acid flame retardants> Examples of phosphinic acid flame retardants include phosphinic acid, dimethylphosphinic acid, methylethylphosphinic acid, methylpropylphosphinic acid, diethylphosphinic acid, dioctylphosphinic acid, phenylphosphinic acid, diethylphenylphosphinic acid, diphenylphosphinic acid, and bis(4-methoxyphenyl)phosphinic acid.
[0032] <Metal hydroxide flame retardants> Examples of metal hydroxide flame retardants include magnesium hydroxide, calcium hydroxide, aluminum hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, titanium hydroxide, zinc hydroxide, copper hydroxide, vanadium hydroxide, tin hydroxide, etc. The metal hydroxide flame retardants may be used alone or in combination of two or more.
[0033] Examples of solid flame retardants other than the above-mentioned solid flame retardants include phosphazenes, metal phosphinates, silicone-based flame retardants, and organic sulfonate-based flame retardants.
[0034] Examples of liquid flame retardants include phosphate flame retardants such as monophosphate and condensed phosphate. Examples of monophosphate esters include, but are not limited to, trimethyl phosphate, triethyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, and tris(β-chloropropyl) phosphate. The condensed phosphate ester is not particularly limited, but examples thereof include resorcinol polyphenyl phosphate (product name: CR-733S), bisphenol A polycresyl phosphate (product name: CR-741), and aromatic condensed phosphate ester (product name: CR747). When a liquid flame retardant is used, the amount is preferably from 1 to 30 parts by mass, and more preferably from 5 to 20 parts by mass, per 100 parts by mass of the urethane resin.
[0035] In addition, the content of the flame retardant other than red phosphorus, i.e., the total content of the above-mentioned solid flame retardant and liquid flame retardant, is not particularly limited, but is preferably 1 to 30 parts by mass, and more preferably 5 to 25 parts by mass, per 100 parts by mass of the urethane resin.
[0036] <Inorganic filler> The foamable urethane resin composition of the present invention may contain an inorganic filler as an additive within a range that does not impair the effects of the present invention. Examples of inorganic fillers include silica, diatomaceous earth, alumina, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, ferrites, basic magnesium carbonate, calcium carbonate, magnesium carbonate, barium carbonate, dawsonite, hydrotalcite, calcium sulfate, barium sulfate, gypsum fiber, potassium salts such as calcium silicate, talc, clay, mica, montmorillonite, bentonite, activated clay, sepiolite, imogolite, sericite, glass fiber, glass beads, silica palan, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon fiber, carbon palan, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, stainless steel fiber, various magnetic powders, slag fiber, fly ash, silica alumina fiber, alumina fiber, silica fiber, zirconia fiber, and the like. From the viewpoint of the foamability of the foamable urethane resin composition, the content of the inorganic filler is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, per 100 parts by mass of the urethane resin.
[0037] The foamable urethane resin composition may further contain additives other than solid flame retardants, liquid flame retardants, and inorganic fillers, and may include, for example, additives such as phenol-based, amine-based, and sulfur-based antioxidants, heat stabilizers, metal damage inhibitors, antistatic agents, stabilizers, crosslinking agents, lubricants, softeners, pigments, and tackifying resins, as well as tackifiers such as polybutene and petroleum resins.
[0038] (Foam stabilizer) The foamable urethane resin composition contains a foam stabilizer. Examples of the foam stabilizer include polyoxyalkylene foam stabilizers such as polyoxyalkylene alkyl ethers, and surfactants such as silicone foam stabilizers such as organopolysiloxanes. The silicone foam stabilizer may also include a graft copolymer of polydimethylsiloxane and polyethylene glycol. The amount of the foam stabilizer in the foamable urethane resin composition is not particularly limited, but is, for example, preferably 0.01 to 3 parts by mass, more preferably 0.05 to 2 parts by mass, and even more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the urethane resin. The foam stabilizer may be used alone or in combination of two or more kinds.
[0039] (foaming agent) Specific examples of the blowing agent include water, low-boiling point hydrocarbons, chlorinated aliphatic hydrocarbon compounds, fluorine compounds, hydrochlorofluorocarbon compounds, hydrofluorocarbons, ether compounds, hydrofluoroolefins, etc. Further examples of the blowing agent include organic physical blowing agents such as mixtures of these compounds, and inorganic physical blowing agents such as nitrogen gas, oxygen gas, argon gas, and carbon dioxide gas. Examples of the low boiling point hydrocarbon include propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and cycloheptane. Examples of the chlorinated aliphatic hydrocarbon compounds include dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, and isopentyl chloride. Examples of the fluorine compound include CHF3, CH2F2, and CH3F. Examples of the hydrochlorofluorocarbon compounds include trichloromonofluoromethane, trichlorotrifluoroethane, and dichloromonofluoroethane (for example, HCFC141b (1,1-dichloro-1-fluoroethane), HCFC22 (chlorodifluoromethane), and HCFC142b (1-chloro-1,1-difluoroethane)). Examples of the hydrofluorocarbon include HFC-245fa (1,1,1,3,3-pentafluoropropane) and HFC-365mfc (1,1,1,3,3-pentafluorobutane). The ether compound may, for example, be diisopropyl ether. Examples of the hydrofluoroolefin include HFO-1233zd(E) (trans-1-chloro-3,3,3-trifluoropropene) and HFO-1234yf (2,3,3,3-tetrafluoro-1-propene).
[0040] The content of the foaming agent is preferably from 0.1 to 30 parts by mass, more preferably from 0.5 to 20 parts by mass, and further preferably from 1 to 15 parts by mass, relative to 100 parts by mass of the urethane resin.
[0041] (catalyst) The foamable urethane resin composition of the present invention contains a catalyst. The catalyst may contain, for example, one or both of a urethanization catalyst and a trimerization catalyst, and preferably contains both. The urethane catalyst is a catalyst that accelerates the reaction between the polyol component and the polyisocyanate. Specific examples of the urethane catalyst include amino compounds, tin compounds, bismuth compounds, and metal salts of acetylacetone. Examples of the amino compound include pentamethyldiethylenetriamine, triethylamine, N-methylmorpholine bis(2-dimethylaminoethyl) ether, bis(2-dimethylaminoethyl) ether, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N'-trimethylaminoethyl-ethanolamine, bis(2-dimethylaminoethyl) ether, N-methyl-N',N'-dimethylaminoethylpiperazine, an imidazole compound in which the secondary amine functional group in the imidazole ring is substituted with a cyanoethyl group, N,N-dimethylcyclohexylamine, diazabicycloundecene, triethylenediamine, tetramethylethylenediamine, tetramethylhexamethylenediamine, 1-methylimidazole, trimethylaminoethylpiperazine, and tripropylamine. Examples of tin compounds include stannous octoate, dibutyltin diacetate, dibutyltin dilaurate, etc. Examples of bismuth compounds include bismuth neodecanoate, bismuth octoate, etc. Examples of acetylacetone metal salts include acetylacetone aluminum, acetylacetone iron, acetylacetone copper, acetylacetone zinc, acetylacetone beryllium, acetylacetone chromium, acetylacetone indium, acetylacetone manganese, acetylacetone molybdenum, acetylacetone titanium, acetylacetone cobalt, acetylacetone vanadium, and acetylacetone zirconium. The urethane resin curing catalyst may be used alone or in combination of two or more kinds.
[0042] The amount of the urethane catalyst in the foamable urethane resin composition is not particularly limited, but is preferably in the range of 0.3 to 10 parts by mass, more preferably in the range of 0.5 to 8 parts by mass, and even more preferably in the range of 1 to 6 parts by mass, relative to 100 parts by mass of the urethane resin. By keeping the amount within the above range, the reaction between the polyol component and the polyisocyanate component can be promoted at an appropriate reaction rate.
[0043] A trimerization catalyst is a catalyst that promotes trimerization to form an isocyanurate bond. By promoting trimerization of a polyurethane resin, the flame retardancy of a polyurethane foam is improved. Examples of the trimerization catalyst that can be used include aromatic compounds such as tris(dimethylaminomethyl)phenol, 2,4-bis(dimethylaminomethyl)phenol, and 2,4,6-tris(dialkylaminoalkyl)hexahydro-S-triazine; alkali metal salts such as potassium acetate, sodium acetate, potassium 2-ethylhexanoate, sodium 2-ethylhexanoate, potassium octylate, and sodium octylate; aziridines such as 2-ethylaziridine; lead compounds such as lead naphthenate and lead octylate; alcoholate compounds such as sodium methoxide; phenolate compounds such as potassium phenoxide; tertiary ammonium salts such as trimethylammonium salts, triethylammonium salts, and triphenylammonium salts; and quaternary ammonium salts such as tetramethylammonium salts, tetraethylammonium, and tetraphenylammonium salts. The trimerization catalyst may be used alone or in combination of two or more kinds.
[0044] The amount of the trimerization catalyst is not particularly limited, but is preferably in the range of 0.5 to 12 parts by mass, more preferably in the range of 1 to 9 parts by mass, and even more preferably in the range of 2 to 5 parts by mass, relative to 100 parts by mass of the urethane resin. By setting the amount of the trimerization catalyst within the above range, isocyanurate bonds are appropriately formed, and flame retardancy is improved. The total amount of the catalyst is preferably 0.5 to 15 parts by mass, more preferably 1 to 12 parts by mass, and even more preferably 2 to 10 parts by mass, per 100 parts by mass of the urethane resin, from the viewpoint of improving the curing speed and flame retardancy of the urethane.
[0045] The foamable urethane resin composition of the present invention is cured by the reaction of the polyol compound and the polyisocyanate compound, and therefore the viscosity of the composition changes with time. Therefore, before using the foamable urethane resin composition, the foamable urethane resin composition is divided into two or more portions to prevent the foamable urethane resin composition from reacting and curing. When using the foamable urethane resin composition, it is preferable to combine the two or more portions of the foamable urethane resin composition into one.
[0046] When the foamable urethane resin composition is divided into two or more components, each of the components of the foamable urethane resin composition divided into two or more components does not start curing alone, and each component may be divided so that the curing reaction starts after each component of the foamable urethane resin composition is mixed. Usually, the foamable urethane resin composition is divided into a polyol composition containing a polyol compound and a polyisocyanate composition containing a polyisocyanate compound.
[0047] The above-mentioned foam stabilizer, blowing agent, catalyst, and additives may be contained in the polyol composition, may be contained in the polyisocyanate composition, or may be provided separately from the polyol composition and the polyisocyanate composition, but are preferably contained in the polyol composition.
[0048] The method for producing the foamable urethane resin composition is not particularly limited, and examples thereof include a method in which a polyol composition and a polyurethane composition are prepared by kneading in advance and then kneading the two, and a method in which each component constituting the foamable urethane resin composition is kneaded, but the foamable urethane resin composition is usually produced by kneading a polyol composition and a polyisocyanate composition. The kneading can be performed by a known method, and for example, the composition can be obtained by kneading using a known device such as a single-screw extruder, a twin-screw extruder, a Banbury mixer, a kneader mixer, a kneading roll, a Raikai mixer, or a planetary stirrer.
[0049] (Viscosity of polyol composition) The viscosity of the polyol composition at 20°C is not particularly limited, but is preferably 2000 mPa·s or less, and is preferably 1000 mPa·s or less. By making the viscosity of the polyol liquid agent below the above upper limit, the fluidity of the foamable urethane resin composition is also good, and mixing failure can be suppressed. From the same viewpoint, the viscosity of the polyol composition at 5°C is not particularly limited, but is preferably 3000 mPa·s or less, and more preferably 1500 mPa·s or less. The viscosity of the polyol composition can be appropriately adjusted, for example, by the molecular weight of the polyol compound used and the amount of the foaming agent. The viscosity of the polyol composition was measured using a B-type viscometer.
[0050] (Application) The use of the foamable urethane resin composition of the present invention is not particularly limited, and it can be used for filling cavities in structures such as buildings, furniture, automobiles, trains, ships, etc., or for spraying onto such structures. Among these, it is preferable to use it for spraying onto structures, i.e., as a foamable urethane resin composition for spraying. Spraying can be performed using a spraying device (e.g., A-25 manufactured by GRACO) and a spray gun (e.g., D-gun manufactured by Gasmar). Spraying can be performed by adjusting the temperature of the polyol composition and the polyisocyanate composition contained in separate containers in the spraying device, causing them to collide and mix at the tip of the spray gun, and turning the mixed liquid into a mist by air pressure. The spraying device and the spray gun are well known, and commercially available products can be used.
[0051] [Polyurethane foam] The polyurethane foam of the present invention is formed from the above-mentioned foamable urethane resin composition, specifically, is obtained by foaming and curing the foamable urethane resin composition. In the polyurethane foam, the sinking distance of the steel ball in the steel ball sinking evaluation is 20 mm or less. If the sinking distance of the steel ball exceeds 20 mm, the polyurethane foam is likely to spread when exposed to a fire or the like, making it difficult to effectively prevent the spread of fire. From the viewpoint of effectively preventing the spread of fire, the sinking distance of the steel ball is preferably 15 mm or less, more preferably 10 mm or less, and further preferably 5 mm or less. The sinking distance of the steel ball is 0 mm or more. The method for evaluating steel ball sinking is as described above. Incidentally, fires caused by polyurethane foam are largely due to sparks and fireballs (lumps of iron heated to high temperatures) during welding and cutting. According to the findings of the present inventors, it has been found that when a fireball comes into contact with polyurethane foam, it melts the resin and advances inside, resulting in the risk of ignition and spread of fire from within the polyurethane foam. The steel ball sinking evaluation reproduces and evaluates fires caused by polyurethane foam during welding and cutting, and can evaluate whether polyurethane foam is resistant to fire spread.
[0052] The density of the polyurethane foam is not particularly limited, but is preferably 20 to 200 kg / m 3 It is preferable that the density is in the range of 200 kg / m 3By setting the density to 20kg / m or less, the polyurethane foam becomes lighter and easier to apply to structures. 3 By setting the density to 25 to 100 kg / m or more, the desired flame retardancy is easily exhibited. From these viewpoints, the density of the polyurethane foam is set to 25 to 100 kg / m 3 More preferably, the range is 25 to 80 kg / m 3 It is more preferable that the density of the polyurethane foam is in the range of 50 / g / cm2. The density of the polyurethane foam can be measured in accordance with JIS K7222. EXAMPLES
[0053] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0054] Details of each component used in each example and comparative example are as follows. (1) Polyol compounds p-Phthalic acid-based polyester polyol (Kawasaki Chemical Industries, Ltd., product name: Maximol RFK-505, hydroxyl value = 250 mg KOH / g) o-Phthalic acid-based polyester polyol (Kawasaki Chemical Industries, Ltd., product name: Maximol RDK-133, hydroxyl value = 315 mg KOH / g) Amine-based polyether polyol (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: DK3776, hydroxyl value = 350 mg KOH / g) Amine-based polyether polyol (manufactured by Sumika Covestro Urethane Co., Ltd., product name: Polyol H422, hydroxyl value = 410 mg KOH / g Sucrose-based polyether polyol (Mitsui Chemicals, product name: Actocol GR84, hydroxyl value = 450 mg KOH / g Ethylenediamine polyether polyol (AGC Corporation, product name: Exenol 750ED, hydroxyl value = 760 mg KOH / g (2) Additives (red phosphorus (flame retardant)) Red phosphorus (Rinkagaku Kogyo, product name: Nova Excel 140) (3) Additives (flame retardants other than red phosphorus) (i) Solid flame retardants Zinc borate (Hayakawa Shoji Co., Ltd., product name: Firebrake ZB) Brominated flame retardant <Ethylenebis(pentabromophenyl)> (manufactured by Albemarle Japan Co., Ltd., product name: SAYTEX8010) (ii) Liquid flame retardants Phosphate ester flame retardant <Tris(β-chloropropyl)phosphate> (manufactured by Daihachi Chemical Industry Co., Ltd., product name: TMCPP) (4) Foam stabilizer Polyalkylene glycol foam stabilizer (Toray Dow Corning, product name: SH-193) (5) Catalyst (i) Trimerization catalyst Quaternary ammonium salt (Tosoh Corporation, product name: TOYOCAT TR20) (ii) Urethane catalyst Imidazole compounds (Tosoh Corporation, product name: TOYOCAT DM70) Bismuth compounds (manufactured by Nitto Kasei, product name: Neostan U600) (6) Foaming agent ·water HFO-1233zd <hydrofluoroolefin> (Honeywell product name: Solstice LBA) (7) Polyisocyanate compounds MDI (manufactured by Sumika Covestro Urethane Co., Ltd., product name: 44V-20)
[0055] The methods for measuring the various physical properties and characteristics are as follows.
[0056] [Steel ball sinking evaluation] For each of the polyurethane foams produced in the Examples and Comparative Examples, the sinking distance of the steel ball was measured by the following procedures (1) to (3). (1) The polyurethane foam was cut into a cube with sides of 50 mm to be used as a test specimen. (2) A wire mesh was placed 30 mm from the burner port of a Bunsen burner (outer flame length 70 mm), and a steel ball with a diameter of 4.7 mm and a weight of 0.44 g was placed on the wire mesh and heated for 7 minutes until the entire steel ball turned red, and the measured temperature of the steel ball was 770° C. LPG combustion gas was used for the Bunsen burner. (3) In an atmosphere of 23°C, the steel ball heated in (2) above was immediately placed on the center of the upper part of the test piece in (1) above and left there until the steel ball had completely sunk in. The test piece was then left at 23°C for 30 minutes to cool sufficiently, after which the cross section was cut and the sinking distance of the steel ball was measured. In addition, a cavity is formed in the test specimen from the top to the inside as the steel ball sinks in. The sinking distance of the steel ball means the maximum distance of the cavity in the vertical direction to the top surface of the test specimen. From the obtained sinking distance of the steel ball, the quality of the flame-resistance property was judged as follows. ◎ The sinking distance of the steel ball is between 0 mm and 10 mm. ○ The sinking distance of the steel ball is more than 10 mm and 20 mm or less × The steel ball sinks in for more than 20 mm.
[0057] [Total heat generation] The total calorific value of the polyurethane foam produced in each Example and Comparative Example was evaluated by the following method. In a polypropylene beaker, a mixture obtained by mixing a polyol compound, a flame retardant, a foam stabilizer, a catalyst, and a blowing agent according to the formulation in Table 1, and a polyisocyanate compound (total amount 200 g, liquid temperature 10°C) were added and stirred with a lab-di-spar for 3 seconds. Immediately after that, the mixture was spread on a gypsum board with a thickness of 12.5 mm to obtain a polyurethane foam. The polyurethane foam adhered to the gypsum board as a base was cut into a length of 10 cm, a width of 10 cm, and a thickness of 3.25 cm (including gypsum board of 12.5 mm) to prepare a cone calorimeter test sample. Using the cone calorimeter test sample, a radiant heat intensity of 50 kW / m was measured in accordance with the test method of ISO-5660. 2 The total heat generated after 5 minutes was measured using a cone calorimeter test when the sample was heated at 40°C for 5 minutes. [Shape transformation] The shape of the cone calorimeter test sample used in measuring the total calorific value was visually observed after 5 minutes had elapsed, and evaluated according to the following criteria. ○ The deformation of the sample in the thickness and width directions is small. In particular, there is no contact with the spark igniter in the thickness direction. △: The deformation of the shape of the sample in the width direction is small, but the deformation in the thickness direction is somewhat large. ×: The sample had a large deformation in the thickness and width directions, which was deemed detrimental to fire prevention.
[0058] [Buckling] The surface of each of the polyurethane foams produced in the Examples and Comparative Examples was pressed with a finger to evaluate the buckling properties. 〇The surface of the foam did not crack or buckle. △: The surface of the foam was partially cracked. × The surface of the foam was cracked and buckled overall.
[0059] [Cure] Approximately 70 g of a mixture obtained by mixing a polyol compound, a polyisocyanate compound, a flame retardant, a foam stabilizer, a catalyst, and a foaming agent according to the formulation in Table 1 was poured into an aluminum mold (length 500 mm x width 180 mm x thickness 20 mm) heated to 40°C and cured for one minute (the length direction was left unfilled). One minute after pouring, the mold was removed and the adhesion of the polyurethane foam to the aluminum plate surface was evaluated visually. ○: No adhesion △: Polyurethane foam adheres to some areas ×: Uncured polyurethane foam adheres to the entire surface, making it difficult to remove from the mold.
[0060] [Elongation rate] Using the same samples as those used to evaluate the curing property, the length of the polyurethane foam after demolding was measured. The lengths of both ends were measured at 20 mm intervals in the width direction (10 points in total including both ends), and the elongation values in the length direction of the mold were averaged. The elongation rate per unit weight was calculated from the average elongation length and the weight of the polyurethane foam. The elongation rate of Example 1 was used as the standard, and those with an elongation rate of less than 90% (poor elongation) were marked with an X, and those with an elongation rate of 90% or more were marked with an ◯.
[0061] [viscosity] The viscosity of the polyol composition was measured at 5° C. using a Brookfield viscometer, simulating winter conditions. Less than 600 mPa·s was rated as ○, and 600 mPa·s or more was rated as ×.
[0062] [Example 1] According to the formulation in Table 1, the polyol compound, the flame retardant (red phosphorus and flame retardants other than red phosphorus), the foam stabilizer, the catalyst, and the foaming agent were weighed into a 1000 mL polypropylene beaker and stirred with a hand mixer at 20°C for 10 seconds to prepare a polyol composition. After that, the polyol composition was cooled to 10°C, and a polyisocyanate composition (polyisocyanate compound) that was also adjusted to 10°C was added to the polyol composition to prepare a foamable urethane resin composition, and the composition was stirred with a lab body spatula for 3 seconds to prepare a polyurethane foam. The polyurethane foam was used to perform the above-mentioned steel ball sinking evaluation and buckling evaluation. In addition, the total heat generation, shape deformation, curing property, and elongation were also evaluated by the above-mentioned procedures. The various evaluation results are shown in Table 1.
[0063] [Examples 2 to 18, Comparative Examples 1 to 2] A polyurethane foam was obtained in the same manner as in Example 1, except that the formulation was changed as shown in Table 1. The polyurethane foam was used to evaluate the steel ball sinking property and the buckling property as described above. The total heat generation, shape deformation, curing property, and elongation were also evaluated by the procedures described above. The various evaluation results are shown in Table 1.
[0064] [Table 1]
[0065] As shown in each example, it was found that the polyurethane foam formed from the foamable urethane resin composition of the present invention has a short steel ball sinking distance, and therefore has properties that make it difficult for fire to spread, is less prone to buckling, and is easy to handle. In contrast, it was found that the polyurethane foams formed from the foamable urethane resin compositions of each comparative example had poor buckling properties, were inferior in handleability, or had a long steel ball sinking distance, and did not have the property of being resistant to fire spread.
Claims
1. A foamable urethane resin composition comprising a polyol compound, a polyisocyanate compound, a foam stabilizer, a foaming agent, a catalyst, and an additive, the additive contains red phosphorus, and the content of the red phosphorus is more than 0 parts by mass and less than 5 parts by mass with respect to 100 parts by mass of the urethane resin composed of the polyol compound and the polyisocyanate compound, A foamable urethane resin composition, wherein a steel ball sinks a distance of 20 mm or less in the steel ball sinking test described below of a polyurethane foam made of the foamable urethane resin composition. (Steel ball sinking evaluation) (1) The polyurethane foam is cut into a cube with sides of 50 mm to prepare a test specimen. (2) A wire mesh is placed 30 mm from the burner port of a Bunsen burner (outer flame length 70 mm), and a steel ball with a diameter of 4.7 mm and a weight of 0.44 g is placed on the wire mesh. The steel ball is heated for at least 5 minutes until the entire ball turns red, and the temperature of the steel ball is increased to 750°C or higher. (3) In an atmosphere of 23° C., the steel ball heated in (2) above is immediately placed on the center of the upper part of the test piece in (1) above and left there until the steel ball has completely sunk in. Then, the cross section of the sufficiently cooled test piece is cut and the sinking distance of the steel ball is measured.
2. The polyurethane foam made of the foamable urethane resin composition was subjected to a test with a radiant heat intensity of 50 kW / m2 in accordance with the ISO-5660 test method. 2 When heated at 40°C, the total heat generated after 5 minutes was 8 MJ / m 2 2. The foamable urethane resin composition according to claim 1, wherein:
3. The foamable urethane resin composition according to claim 1 or 2, wherein the catalyst comprises a trimerization catalyst.
4. 4. The foamable urethane resin composition according to claim 1, having an isocyanate index of 200 to 700.
5. The foamable urethane resin composition according to any one of claims 1 to 4, wherein the additive contains a solid flame retardant other than red phosphorus, and a total content of the red phosphorus and the solid flame retardant other than red phosphorus is 0.5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the urethane resin composed of the polyol compound and the polyisocyanate compound.
6. The foamable urethane resin composition according to any one of claims 1 to 5, wherein the polyol compound is an aromatic polyol compound.
7. The foamable urethane resin composition according to claim 6, wherein the aromatic polyol compound contains at least one of a phthalic acid-based polyester polyol and an amine-based polyether polyol.
8. A polyurethane foam formed from the foamable urethane resin composition according to any one of claims 1 to 7, wherein the steel ball has a sinking distance of 20 mm or less in the steel ball sinking evaluation.
Citation Information
Patent Citations
Composition for flame retarding rigid polyurethane foam
JP1998168150A
Fire-resistant urethane resin composition
JP2014193995A
Thermally stable, flame-retardant, flexible polyurethane foam
JP2014527093A
Urethane resin composition
JP2015063676A
Flame resistant heat insulation composition
JP2015078357A